Composition and Mineralogical Features of Ultramafic Rocks of Eastern Part of Southern Kraka Massif (South Urals) - D. E. Saveliev; A. I. Biembetov; T. D. Shabutdinov; A. A. Samigullin; R. A. Gataullin (Georesursy, 2024)
The paper presents new data on the structure and composition of ultramafic rocks in the eastern part of the South Kraka massif. It is shown that the studied area is composed predominantly of spinel peridotites, among which the main role belongs to lherzolites with a low content of clinopyroxene (2–5%) and harzburgites, among which lens-shaped and bandshaped inclusions of monomineral olivine rocks – dunites – are quite often observed. The leading role in the structure of the rocks belongs to high-Mg olivine (Fo87-94), a secondary role (2016). Nature of the lithospheric mantle beneath the Arabian Shield and genesis of Al-spinel micropods: Evidence from the mantle xenoliths of Harrat is played by high-Mg orthopyroxene (enstatite) and Ca-Mg clinopyroxene diopside. Rare minerals of the mantle stage are amphibole and plagioclase. A typical accessory mineral of ultramafic rocks is spinel, the composition of which varies from high-Al in lherzolites (Cr# = 0.16–0.3), to moderate-Al in harzburgites (Cr# = 0.3–0.55) and to high-Cr in dunites (Cr# = 0.6–0.85). Of the rare accessory minerals in the rocks, the following were identified: native copper, pentlandite, awaruite and PGM (laurite, irarsite, Os-Ir-Ru-alloys). The section of mantle ultramafic rocks of the Sargan Range completed its high-temperature evolution to the levels of the plagioclase peridotite facies, partly in the transition zone from spinel to plagioclase facies. An assessment of oxygen fugacity allows us to speak about more reducing conditions for the formation of rocks of the studied area compared to other similar formations of upper mantle origin and allows us to classify the studied ultramafic rocks as moderately depleted restites of the upper mantle under the riftogenic structure of the Paleo-Ural basin. The geochemical specialization of PGM also indicates a restite origin of ultramafic rocks. At the stage of cooling and tectonic transformations in the crust, ultramafic rocks underwent serpentinization.